Weights balancing method using entropy values in solving MCDM problem - Krylovas, Aleksandras; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2016)
The article shows how multiple criteria optimization problems could be solved by application of modified KEMIRA method, when there are three groups of criteria. Criteria priorities are determined by the entropy, criteria weights are calculated by solving optimization task. The proposed method allows to find one of several possible local extrema.